Pengaruh Efektivitas Pengendalian Internal, Kesesuaian Kompensasi, dan Moralitas Individu Terhadap Kecenderungan Kecurangan (Fraud) pada Lembaga Perkreditan Desa di Kecamatan Kerambitan - Ni Kadek Sri Ayu Ulandari; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2022)
F Fraud is a type of purposeful behavior where one individual harmed another party. The company will go bankrupt if fraud is permitted to continue. Understanding the negative effects is crucial for businesses to prevent various types of fraud that could happen within the organization. This study was carried out to examine the variables that affect the likelihood of fraud, including the effectiveness of internal controls, the appropriateness of compensation, and individual morality. 98 respondents from the Village Credit Institution in Kerambitan District were included in the research samples. Multiple linear regression analysis approaches will be used to examine research data in the future. The findings of this study suggest that internal control efficiency, appropriateness of remuneration